ANALISIS IMPLEMENTASI SKEMA DUAL RESIDENT ENTITIES DI INDONESIA - Kumalasari, Kartika Putri; Dewanti, Dania; Egalita, Filzah Farah; Mumtadz, Adhisa Qotrunnada; Azhari, Firman Khoirulhadi (FIA UB, 2022)
This research focuses on the implementation of dual resident entities in Indonesia. The purpose of this study was to determine the implementation of a policy referring to George Edward III's theory, namely communication, resources, disposition and bureaucratic structure and to know and discuss the SWOT analysis of the application of dual resident entities in Indonesia. This type of research uses a descriptive qualitative approach. Data collection techniques come from interviews and documentation. The analytical method used is the data analysis method of the Miles and Huberman model. The results of this study indicate that the implementation of dual resident entities in Indonesia based on George Edward III's theory is mostly appropriate according to the theory, namely resources, disposition, and bureaucratic structure. However, it is not appropriate with the indicator communication.